Programmable Logic Controller (PLC): Literature Review - Ricky Permadi; M Agung Trijayadi; Owen Mulya; Rizky Ramadhani; Akbar Maulana Yusuf; Hibarkah Kurnia (Publika Bersama Nusantara, 2026)
Programmable Logic Controllers (PLCs) are essential components in industrial automation, serving as the backbone for controlling, monitoring, and integrating intelligent systems. Despite their widespread adoption, PLC implementation faces several challenges, including limited flexibility in manual programming, interoperability barriers with Industry 4.0 systems, cybersecurity risks, and constraints in real-time data processing. This study aims to conduct a comprehensive literature review on the development, implementation, and innovation of PLCs, focusing on the integration of intelligent technologies such as Large Language Models (LLMs), digital twins, predictive root cause analysis, and IoT, as well as PLC applications in technical education. The research method involved identification and selection of relevant literature from Scopus, IEEE Xplore, ScienceDirect, and ACM Digital Library, followed by data extraction on issues, objectives, methods, subjects, findings, and conclusions of each study, and qualitative analysis to identify trends, advantages, and challenges in PLC development. The results indicate that innovations such as LLM-based code automation, digital twin integration for production monitoring, and PLC-based learning simulators can significantly improve efficiency, accuracy, reliability, and system adaptability. Additionally, communication modules, adaptive interfaces, and network integration capabilities are critical for supporting modern industrial automation. This study provides a comprehensive understanding of the evolution, potential, and limitations of PLCs in enabling secure, efficient, and sustainable automation.